Applying ludic in the classroom when teaching Industrial Engineering. Case Engineering of Methods (2019)
If I hear, I forget; if I see, I remember; if I do,I learn (Chinese Proverb). This paper includes a classroomdynamic ludic based on activities like microworlds and howthey are important for the social construction of knowledgeand for the student learning. It proposes a pedagogical toolthat complements traditional teaching methodology currentlyused in the classrooms of Colombian Universities, applyingthe methodology proposed by GEIO’s researching group forthe course called Engineering of Methods for the IndustrialEngineering Faculty at Universidad Tecnológica de Pereira. Itdevelops qualitative analysis tools such as Grounded Theory inorder to interpret the results of this study